PENGARUH PENGAMBILAN KEPUTUSAN DAN KOMUNIKASI ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT GIFAS JAYA SENTOSA TANGERANG SELATAN - Saryana, Saryana; Nanda Rodiyana (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of decision-making and organizational communication on employee job satisfaction at PT Gifas Jaya Sentosa, South Tangerang. The independent variables in this research consist of decision-making (X₁) and organizational communication (X₂), while the dependent variable is job satisfaction (Y). The research employed a quantitative approach by distributing questionnaires to 154 employees as respondents. Data analysis techniques included validity and reliability tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²) using SPSS v.30. The results indicate that decision-making has a significant partial influence on job satisfaction, with a significance value of 0.009 < 0.05. Organizational communication also has a significant partial influence on job satisfaction, with a significance value of < 0.001 < 0.05. Simultaneously, both variables significantly influence job satisfaction, as shown by a significance value of < 0.001 < 0.05. The coefficient of determination (R²) of 0.621 indicates that 62.1% of the variation in job satisfaction is explained by decision-making and organizational communication, while the remaining 37.9% is influenced by other factors outside this study. In conclusion, employee job satisfaction at PT Gifas Jaya Sentosa can be improved through participatory decision-making and effective internal communication. Strengthening internal communication and involving employees in organizational decisions are recommended to enhance employee satisfaction and loyalty.